Understanding the Stability of Poorly Covered Pickering Emulsions Using on‐Chip Microfluidics - Xuefeng Shen; Chang Chen; Berend van der Meer; Thomas E. Kodger; Uddalok Sen; Siddharth Deshpande; Jasper van der Gucht (Advanced Science)
Abstract Particle‐stabilized emulsions, also known as Pickering emulsions, have shown promise in areas that require long‐term stability with minimum use of surfactants. While most work has focused on densely covered Pickering emulsions, such emulsions are known to retain stability even when the interfaces are sparsely covered with particles. Here, the formation, dynamics, and stability of poorly covered model Pickering emulsions are studied in a controlled manner by utilizing a microfluidic platform. The formed Pickering emulsions remain highly stable, over at least 12 h, even with a surface area coverage below 3%. By directly visualizing the droplet interface at various stages, the exceptional stability is attributed to the highly spatially heterogeneous distribution of adsorbed particles which exclusively form particle bridges at the contact point between the droplets. Remarkably, these bridges are assembled in the form of crowns between the droplet interfaces, as visualized by confocal microscopy. The assembly behavior of the adsorbed particles in response to hydrodynamic forces and the formation of non‐uniform particle distribution are discussed by analyzing the different forces present during emulsification, corroborated by numerical simulations. In conclusion, using a lab‐on‐a‐chip approach, this work provides further understanding toward the fabrication of Pickering emulsions via preferential interfacial localization of particles.